(untitled) (UUM Journal of Legal Studies, 2026)
Non-Revenue Water (NRW) poses a significant challenge to water utilities worldwide, particularly in developing countries where infrastructure and regulatory systems are often inadequate. Malaysia continues to face high levels of NRW compared to its regional neighbours. This paper examines the effectiveness of Malaysia’s legal frameworks and enforcement strategies in addressing NRW, focusing on the Water Services Industry Act 2006 (WSIA 2006) and related regulations. Through a detailed legal analysis, the study evaluates the strengths and weaknesses of Malaysia’s current regulatory environment and enforcement mechanisms. It also compares these strategies with Singapore’s highly successful regulatory practices to provide insights into how Malaysia can improve its NRW management. The findings indicate that while Malaysia has established a comprehensive legal framework for NRW reduction, inconsistent implementation and limited enforcement capacity significantly undermine its effectiveness. Drawing on Singapore’s proactive approach, this paper recommends strengthening regulatory oversight, improving financial and technical support for water operators, and leveraging advanced technologies to enhance NRW management. These measures are essential to achieving sustainable water management and ensuring the financial viability of Malaysia’s water utilities.